1996
DOI: 10.1111/j.1467-8624.1996.tb01793.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Work Intensity on Adolescent Mental Health, Achievement, and Behavioral Adjustment: New Evidence from a Prospective Study

Abstract: This article examines the effects of work intensity on adolescent mental health, academic achievement, and behavioral adjustment. Questionnaire data were collected yearly from an initial panel of 1,000 randomly selected ninth graders (14-15 years old). Consistent with other studies, students who worked at higher intensity engaged in more alcohol use. The methodological strengths of this research (a representative panel studied prospectively over a 4-year period with minimal attrition and an analysis incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
146
3
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(162 citation statements)
references
References 34 publications
9
146
3
4
Order By: Relevance
“…Several outcomes of adolescent work intensity and experiences have been empirically examined: (a) work-related cognitions, including vocational self-efficacy, occupational values, work motivation, cynicism about work, and job satisfaction (e.g., Brooks, Cornelius, Greenfield, & Joseph, 1995;Mortimer, Dennehy, & Lee, 1991;Mortimer, Finch, Ryu, & Shanahan, 1996;Stern et al, 1990); (b) family-related outcomes, including interactions (mother's hostility, adolescent's hostility at home, sharing of advice, closeness to parents, frequency of joint activities such as dinners together, arguments with parents), autonomy (parental monitoring, chores at home, and independent decision-making regarding purchases, dating and curfew), and time with the family (e.g., Mortimer & Shanahan, 1994;Shanahan, Elder, Burchinal, & Conger, 1996;; (c) schoolrelated outcomes, including grades, absences, time spent on homework, and class-cutting (e.g., Barling, Rogers, & Kelloway, 1995;Mael, Morath, & McLellan, 1997;Schoenhals, Tienda, & Schneider, 1998;; (d) time allocation, including extracurricular activities, dating, time spent reading and watching television (e.g., Schoenhals et al, 1998); (e) psychological functioning, including selfconcept crystallization, mastery, depressive affect, satisfaction with life and leisure, dependability, self-esteem, and self-reliance (e.g., Barling et al, 1995;Brooks et al, 1995;Greenberger, 1988;; (f) problem behaviors, including substance use, delinquent acts such as cheating and trouble with police, and victimization (e.g., McMorris & Uggen, 2000;; (g) health behaviors, such as sleep, eating breakfast, and exercise (e.g., ; and (h) postsecondary educational attainments, job training, employment stability and earnings (e.g., Creed, Muller & Patton, 2003;Mael et al, 1997;Mortimer, Staff, & Oesterle, 2003;Stern & Nakata, 1991).…”
Section: Adolescent Work Behavior and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several outcomes of adolescent work intensity and experiences have been empirically examined: (a) work-related cognitions, including vocational self-efficacy, occupational values, work motivation, cynicism about work, and job satisfaction (e.g., Brooks, Cornelius, Greenfield, & Joseph, 1995;Mortimer, Dennehy, & Lee, 1991;Mortimer, Finch, Ryu, & Shanahan, 1996;Stern et al, 1990); (b) family-related outcomes, including interactions (mother's hostility, adolescent's hostility at home, sharing of advice, closeness to parents, frequency of joint activities such as dinners together, arguments with parents), autonomy (parental monitoring, chores at home, and independent decision-making regarding purchases, dating and curfew), and time with the family (e.g., Mortimer & Shanahan, 1994;Shanahan, Elder, Burchinal, & Conger, 1996;; (c) schoolrelated outcomes, including grades, absences, time spent on homework, and class-cutting (e.g., Barling, Rogers, & Kelloway, 1995;Mael, Morath, & McLellan, 1997;Schoenhals, Tienda, & Schneider, 1998;; (d) time allocation, including extracurricular activities, dating, time spent reading and watching television (e.g., Schoenhals et al, 1998); (e) psychological functioning, including selfconcept crystallization, mastery, depressive affect, satisfaction with life and leisure, dependability, self-esteem, and self-reliance (e.g., Barling et al, 1995;Brooks et al, 1995;Greenberger, 1988;; (f) problem behaviors, including substance use, delinquent acts such as cheating and trouble with police, and victimization (e.g., McMorris & Uggen, 2000;; (g) health behaviors, such as sleep, eating breakfast, and exercise (e.g., ; and (h) postsecondary educational attainments, job training, employment stability and earnings (e.g., Creed, Muller & Patton, 2003;Mael et al, 1997;Mortimer, Staff, & Oesterle, 2003;Stern & Nakata, 1991).…”
Section: Adolescent Work Behavior and Developmentmentioning
confidence: 99%
“…When examining the outcome of mental health, there is little evidence that working, or even the intensity of work, is associated (Bachman, Bare, & Frankie, 1986;Mortimer et al, 1996;Mortimer & Kirkpatrick Johnson, 1998). Instead, adolescents' distress may be associated with difficulties entering the labor market.…”
Section: Adolescent Work Behavior and Developmentmentioning
confidence: 99%
“…Diversas investigaciones sobre las consecuencias del empleo estudiantil se han centrado en las implicaciones del carácter selectivo de las actividades laborales (Mortimer, Finch y Ryu, 1996;Mortimer, 2001;Warren y Lee, 2003;Entwisle, Alexander y Steffel, 2005). Mortimer et al (1996) llaman la atención sobre la necesidad de ir más allá de las horas trabajadas y atender la naturaleza del trabajo realizado, ya que algunos tipos de empleo pueden ser más benéficos que otros al fomentar el desarrollo de ciertas habilidades o aumentar las aspiraciones educativas, incluso cuando los jóvenes invierten más horas de trabajo.…”
Section: El Tipo De Empleo De Los Estudiantesunclassified
“…Mortimer et al (1996) llaman la atención sobre la necesidad de ir más allá de las horas trabajadas y atender la naturaleza del trabajo realizado, ya que algunos tipos de empleo pueden ser más benéficos que otros al fomentar el desarrollo de ciertas habilidades o aumentar las aspiraciones educativas, incluso cuando los jóvenes invierten más horas de trabajo.…”
Section: El Tipo De Empleo De Los Estudiantesunclassified
“…Lillydahl (1990) reported that working up to 13.5 hours per week has a positive effect on GPA. Mortimer et al (1996) found that high school seniors who worked less than 20 hours per week have higher grades compared to nonworking students. D'Amico (1984) concluded that school-year employment didn't affect high school rank.…”
Section: Introductionmentioning
confidence: 99%